EXPLORING NURSES’ KNOWLEDGE OF THE GLASGOW COMA SCALE IN INTENSIVE CARE AND EMERGENCY DEPARTMENTS AT A TERTIARY HOSPITAL IN RIYADH CITY, SAUDI ARABIA - Abdulrhman Albougami, (The Malaysian Journal of Nursing (MJN), 2019)
Purpose: The present study determines the factors affecting knowledge of the Glasgow Coma Scale (GCS) of emergency room (ER) and intensive care unit (ICU) nurses who work at a tertiary hospital in Riyadh, Saudi Arabia. Methods: A cross-sectional study with self-administered questionnaire was conducted among 149 ICU and ER nurses conveniently selected at a tertiary hospital in Saudi Arabia. A standardized tool was used to assess knowledge of the GCS. The study adhered to the STROBE guideline for cross-sectional studies. Results: Expatriate nurses (p<0.001) and those with a postgraduate degree (p<0.05) were found to have more knowledge of the GCS. Nurses with expertise in ICU services scored significantly higher (p<0.001) than those who work in the ER. Nurses reporting no previous training in the GCS had higher scores (p<0.05) than those who had previous training in the GCS. Conclusion: Some of the demographic characteristics and nurses’ knowledge about the GCS were associated. Expatriate, postgraduate, and ICU nurses were more knowledgeable about the GCS tool. Surprisingly, nurses without GCS additional training had more GCS knowledge than nurses who had attended training. The results provide valuable insights into and guidance for improving GCS knowledge among ICU and ER nurses.